Risk factors for erectile Dysfunction. Urology consultation at Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2017)
A cross-sectional descriptive study was conduced in order to determine the risk factors for erectile dysfunction in patients attending urology clinic of the Hospital Central Universitario Dr. "Antonio Maria Pineda". To do this, a sample of 255 patients was selected, finding out that 51.94% had erectile dysfunction according to the Sexual Health Inventory for Men, of which 25.97% was mild, 14.73% mild-moderate 7.36% moderate and 3.87% severe. In addition, this group of patients was characterized by an average age of 60.94 ± 8.18 years. The psychobiological habits like smoking and alcohol consumption showed no statistical differences (p> 0.05). Meanwhile, the most common vascular risk factors were hypertension (51.49%), obesity (26.87%), diabetes mellitus (21.64%) and dyslipidemia (17.91%). However, hypertension and diabetes mellitus were statistically significant. In relation to pharmacological risk, 50% were receiving antihypertensive drugs (23.88% Amlodipine and 20.89% Losartan). Moreover, only 7.46% presented neurogenic risk factors. With regard to the Lower Urinary Tract Symptoms (LUTS) 43.28% were moderate, 31.34% mild and 21.64% severe (p: 0.0173). Also, prostatic enlargement by ultrasound was 36.57% grade II, 29.10% grade I and 25.37% grade III, with an average prostate volume of 47.31 ± 26.43 ml. Thus, it was possible to obtain information on the risk factors associated with erectile dysfunction, confirming that it is a multi-causal problem.
Keywords: Erectile dysfunction; Risk factors; Sexual Health Inventory for Men